Bearing capacity of stabilized peat column using hand operated cone penetrometer - Shahidul Islam, M.; Hashim, Roslan (2009)
The main objective of this study is to stabilize peat soil by deep mixing method using cement, sand, benlonite and calcium chloride as binder and to determine the effect on bearing capacity using proving ring hand operated cone penetrometer. Eight soil-binder columns have been constructed by mixing auger and prebored and premixing method using two different combination of binder. Bearing capacity of the columns has been evaluated by hand operated cone penetrometer after 1, 3, 7, 14 and 28 days of curing time. From the test results it was observed thai bearing capacity of peal column increased considerably after stabilization.